Endogenous growth with a limited fossil fuel extraction capacity - Gilbert Kollenbach (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2014)
Campbell (1980) and following authors have disussed a limited resoure extration capacity as an augmentation of the well-known Hotelling model. We integrate a limited extraction capacity and related investments in the endogenous growth model of Tsur & Zemel (2005) to study its effect on economic development. The capacity constraint gives raise to three effects. On the one hand, higher energy costs and the reallocation of production towards capacity investments decrease production available for consumption, research and/or general capital investments (energy cost and reallocation effect). On the other hand, research investments may increase, which boosts available production (research effect). Depending on the general capital endowment and the strength of the effects, long-run consumption may be boosted or depressed. In particular, the capacity constraint rationalizes the "curse of natural resources" phenomenon. Furthermore, we find that capacity investments may be postponed to later points in time, if the general capital endowment is very high.
Keywords: Q32; Q42; O41; 330; exhaustible resoures; limited extraction capacity; endogenous growth